A no-arbitrage analysis of macroeconomic determinants of term structures and the exchange rate - Fousseni Chabi-Yo; Jun Yang (Bank of Canada, 2007)
We study the joint dynamics of macroeconomic variables, bond yields, and the exchange rate in an empirical two-country New-Keynesian model complemented with a no-arbitrage term structure model. With Canadian and US data, we are able to study the impact of macroeconomic shocks from both countries on their yield curves and the exchange rate. The variance decomposition of the yield level shows that the US monetary policy and aggregate supply shocks explain a majority of the unconditional variations in Canadian yields. They also explain up to 50% of the variations in the expected excess holding period returns of Canadian bonds. In addition, Canadian monetary policy shocks explain more than 70% of the variations in Canadian yields over short and medium forecast horizons. It also explains around 40% of the expected excess holding period returns of Canadian bonds. Both Canadian and US macroeconomic shocks help explain the dynamics of the exchange rate and the time-varying exchange risk premium.
Keywords: E12; E43; F41; G12; G15; 330; Debt management; Exchange rates; Interest rates; Financial markets; Econometric and statistical methods; Wirtschaftslage; Schock; Kapitalertrag; Wechselkurs; Zinsstruktur; Zwei-Länder-Modell; Kanada; USA